18F Fluorocholine Dynamic Time-of-Flight PET/MR Imaging in Patients with Newly Diagnosed Intermediate- to High-Risk Prostate Cancer: Initial Clinical-Pathologic Comparisons - Choi, Joon Young; Yang, Jaewon; Noworolski, Susan M; Behr, Spencer; Chang, Albert J; Simko, Jeffry P; Nguyen, Hao G; Carroll, Peter R; Kurhanewicz, John; Seo, Youngho (Radiology, 2017)
Purpose To investigate the initial clinical value of fluorine 18 (18F) fluorocholine (FCH) dynamic positron emission tomography (PET)/magnetic resonance (MR) imaging by comparing its parameters with clinical-pathologic findings in patients with newly diagnosed intermediate- to high-risk prostate cancer (PCa) who plan to undergo radical prostatectomy. Materials and Methods The institutional review board approved the study protocol, and informed written consent was obtained from all subjects for this HIPAA-compliant study. Twelve men (mean age ± standard deviation, 61.7 years ± 8.4; range, 46-74 years) with untreated intermediate- to high-risk PCa characterized according to Cancer of the Prostate Risk Assessment (CAPRA) underwent preoperative FCH dynamic PET/MR imaging followed by radical prostatectomy between April and November 2015. PET/MR imaging parameters including average and maximum K1 (delivery rate constant) and standardized uptake values (SUVs) and Prostate Imaging Reporting and Data System (PI-RADS) version 2 scores were measured and compared with clinical-pathologic characteristics. For statistical analysis, the Spearman rank correlation and Mann-Whitney U tests were performed. Results Of the PET parameters, maximum SUV of primary tumors showed significant correlations with several clinical-pathologic parameters including serum prostate-specific antigen level (ρ = 0.71, P = .01), pathologic stage (ρ = 0.59, P = .043), and postsurgical CAPRA score (ρ = 0.72, P = .008). The overall PI-RADS score showed significant correlations with pathologic tumor volume (ρ = 0.81, P < .001), percentage of tumor cells with Gleason scores greater than 3 (ρ = 0.59, P = .02), and postsurgical CAPRA score (ρ = 0.58, P = .046). The high-risk postsurgical CAPRA score patient group had a significantly higher maximum SUV than did the intermediate-risk group. Combined PET and MR imaging showed improved sensitivity (88%) for prediction of pathologic extraprostatic extension compared with that with MR imaging (50%) and PET (75%) performed separately. Conclusion Maximum SUVs and PI-RADS scores from FCH PET/MR imaging show good correlation with clinical-pathologic characteristics, such as postsurgical CAPRA score, which are related to prognosis in patients with newly diagnosed intermediate- to high-risk PCa. © RSNA, 2016 Online supplemental material is available for this article.Purpose To investigate the initial clinical value of fluorine 18 (18F) fluorocholine (FCH) dynamic positron emission tomography (PET)/magnetic resonance (MR) imaging by comparing its parameters with clinical-pathologic findings in patients with newly diagnosed intermediate- to high-risk prostate cancer (PCa) who plan to undergo radical prostatectomy. Materials and Methods The institutional review board approved the study protocol, and informed written consent was obtained from all subjects for this HIPAA-compliant study. Twelve men (mean age ± standard deviation, 61.7 years ± 8.4; range, 46-74 years) with untreated intermediate- to high-risk PCa characterized according to Cancer of the Prostate Risk Assessment (CAPRA) underwent preoperative FCH dynamic PET/MR imaging followed by radical prostatectomy between April and November 2015. PET/MR imaging parameters including average and maximum K1 (delivery rate constant) and standardized uptake values (SUVs) and Prostate Imaging Reporting and Data System (PI-RADS) version 2 scores were measured and compared with clinical-pathologic characteristics. For statistical analysis, the Spearman rank correlation and Mann-Whitney U tests were performed. Results Of the PET parameters, maximum SUV of primary tumors showed significant correlations with several clinical-pathologic parameters including serum prostate-specific antigen level (ρ = 0.71, P = .01), pathologic stage (ρ = 0.59, P = .043), and postsurgical CAPRA score (ρ = 0.72, P = .008). The overall PI-RADS score showed significant correlations with pathologic tumor volume (ρ = 0.81, P < .001), percentage of tumor cells with Gleason scores greater than 3 (ρ = 0.59, P = .02), and postsurgical CAPRA score (ρ = 0.58, P = .046). The high-risk postsurgical CAPRA score patient group had a significantly higher maximum SUV than did the intermediate-risk group. Combined PET and MR imaging showed improved sensitivity (88%) for prediction of pathologic extraprostatic extension compared with that with MR imaging (50%) and PET (75%) performed separately. Conclusion Maximum SUVs and PI-RADS scores from FCH PET/MR imaging show good correlation with clinical-pathologic characteristics, such as postsurgical CAPRA score, which are related to prognosis in patients with newly diagnosed intermediate- to high-risk PCa. © RSNA, 2016 Online supplemental material is available for this article.